Development of rule based approach for assessment of off-road trafficability using remote sensing and ancillary data. (20th February 2021) - Pundir, Sunil Kumar; Garg, Rahul Dev
Abstract: Off-road trafficability is one of the most important factors during military operations. Primarily, there are four factors like landuse, soil type, slope and moisture, which are responsible for predicting off-road trafficability. In the present study, multi-level approach leading from landform, land use to terrain factors was used to assess the obstacle induced towards the cross country movement of tracked and wheeled vehicle separately. The information of land use, landform and slope was gathered from space based sensors, while for soil and moisture information, the field samples analysis along with ancillary information was also used other than space based sensors. The main aim of this study is to make the rule based assessment of terrain in categorization of off-road trafficability in four categories of movement like good, restricted, restricted with engineering measures and difficult. This will improve the speedy assessment of off-road trafficability of inaccessible terrain in the many countries around the world.